Engineering and Application of Pluripotent Stem Cells - Martin, Ulrich; Zweigerdt, Robert; Gruh, Ina (Advances in Biochemical Engineering/Biotechnology, 2018)
This book reviews the latest biotechnological advances with pluripotent stem cells, exploring their application in tissue engineering and medicinal chemistry. Chapters from expert contributors cover topics such as the production of transgene-free induced pluripotent stem cells (iPSCs), expansion, controlled differentiation and programming of pluripotent stem cells, and their genetic instability. Particular attention is given to the application of the pluripotent stem cells for vascularision of engineered tissue and for drug screening. This book will appeal to researchers working in regenerative medicine and drug discovery, and to bioengineers and professionals interested in stem cell research.